1989
DOI: 10.1109/29.31291
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear smoothing filters based on rank estimates of location

Abstract: Abstracf-A class of nonlinear filters is introduced, which is based on the rank estimates (R-estimate\) of location parameters in statistical theory. We show first how moving-window rank filters (R-filters) can be defined starting from rank estimates of location. These filters utilize the relative ranks of the observations in each window to produce a n output value. A special class of rank filters produces outputs which a r e medians of selected pairwise averages of observations inside each ~i n d o w .The Wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Asymptotic normality under dependent sampling and neural network implementations of these tests were investigated in [10]. Rank and order statistics as well as robust partition tests have been used in the past for parameter estimation and filter implementations [12].…”
Section: The Generalized Quantile Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Asymptotic normality under dependent sampling and neural network implementations of these tests were investigated in [10]. Rank and order statistics as well as robust partition tests have been used in the past for parameter estimation and filter implementations [12].…”
Section: The Generalized Quantile Testsmentioning
confidence: 99%
“…Each recursion requires ~3N multiplications. After the parameters above are specified, the scores are estimated from (12). Computation of the efficacy from (8) requires ~M(M-1) multiplications because the involved matrices are symmetric.…”
Section: System Complexitymentioning
confidence: 99%
“…When the noise is impulsive, non-linear schemes are reported to be suitable for mitigating the effects of noise components in many signal processing applications [11]- [14]. In particular, it has been diversely shown that non-linear schemes which employ both non-linear and linear operations can successfully suppress the influence of noise components in both Gaussian and impulsive environment [11]- [13]. Providing reasonable performance in both Gaussian and impulsive noise environment, order statistics of the averages of observations [11], [13] and averages of the order statistics of observations [12] are used for a variety of applications including signal detection and signal restoration.…”
Section: Preliminariesmentioning
confidence: 99%
“…These are based on another large class of robust estimators, the so-called R estimators [7], [8], [127]. The most important R filter is the Wilcoxon filter [128] …”
Section: E R Filtersmentioning
confidence: 99%